Observations on Muscidifurax zaraptor Kogan & Legner and Nasonia vitripennis (Walker) (Hymenoptera Chalcidoidea Pteromalidae) parasitoids of Musca domestica L. (Bollettino di zoologia agraria e bachicoltura, 2024)
Influence of temperature and humidity on development and on search capability and parasitization of Musca domestica pupae, at different depths of organic clay loam, of Muscidifurax zaraptor Kogan & Legner and Nasonia vitripennis (Walker) was studied. Developmental period is longer at 20°C than at 27°C in both species. The mean developmental period of M. zaraptor is not significantly different varying r.h. (40-60-80±5%). N. vitripennis has similar behaviour, except at 20°Cand 40±5% r.h.. M. zaraptor shows a greater ability than N. vitripennis in locating and parasitizing M. domestica pupae at different depths (1, 2, 3 cm).
Keywords: Muscidifurax zaraptor; Nasonia vitripennis; Musca domestica; parasitization; depths